Predicting job satisfaction of mental health peer support workers (PSWs). Issue 6 (2nd November 2018) - Clossey, Laurene; Solomon, Phyllis; Hu, Chin; Gillen, James; Zinn, Miranda
ABSTRACT: The Mental Health Recovery Model is an empowering service philosophy which has been transforming the field of mental health. An important service approach to actualizing this model is hiring peer support workers (PSWs) who are peers advanced in recovery and employed to assist other peers in their recovery process. This study reports on factors hypothesized to affect PSW job satisfaction. Using multiple regression analyses, organizational culture and relationship with peers predicted 29% of job satisfaction. Based on these findings, suggestions are offered to assist social work administrators in effectively integrating and supporting PSWs in the workplace.